2021
DOI: 10.1097/mpa.0000000000001707
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Gastroenteropancreatic Neuroendocrine Tumor Treatment and Survival in the United States

Abstract: ObjectivesThe objective of this study was to evaluate racial differences in cancer treatment and survival in gastroenteropancreatic neuroendocrine tumor (GEP-NET) patients.MethodsUsing the Surveillance, Epidemiology, and End Results Registry, we identified patients with GEP-NETs of the stomach, small intestine (SI), colon, rectum, appendix, and pancreas diagnosed between 1973 and 2014. Demographic, cancer, and treatment information were collected and compared using χ2tests. Multivariable logistic and Cox regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Notably, Kessel et al have reported similar racial disparities in the US; rectal NENs were more likely to occur in Asians and African Americans, but less likely to occur in Whites. In contrast, small intestinal NENs were common in Whites, African Americans, and Hispanics but rare in Asians [ 27 ]. This phenomenon suggests that there might be an association between genetic background and the biological characteristics of GEP-NENs.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, Kessel et al have reported similar racial disparities in the US; rectal NENs were more likely to occur in Asians and African Americans, but less likely to occur in Whites. In contrast, small intestinal NENs were common in Whites, African Americans, and Hispanics but rare in Asians [ 27 ]. This phenomenon suggests that there might be an association between genetic background and the biological characteristics of GEP-NENs.…”
Section: Epidemiologymentioning
confidence: 99%
“…USA: United States of America. Data for the figure is based on references [ 12 , 16 , 17 , 18 , 21 , 22 , 23 , 27 ].…”
Section: Figurementioning
confidence: 99%
“…2 Most GEP-NENs are diagnosed between the ages of 55 and 69, although colonic NENs peak after age 70. 3 However, across all GEP-NENs, White patients are diagnosed at significantly older ages compared to all other ethnoracial groups. Notably, an analysis of the SEER database found that the incidence of GEP-NEN varies significantly among ethnoracial groups, occurring more frequently in Black patients (5.19 cases per 100,000 individuals) compared to other ethnoracial groups (White 3.05; ethnically Hispanic/Latinx 2.46; others 2.39).…”
Section: Introductionmentioning
confidence: 99%
“…4 Additional analyses have found significant differences in the rate of metastatic disease among racial groups, with Black patients having the highest rate of advanced stage/metastatic disease in pancreatic, gastric, and appendiceal, NENs (36.3%, 20.9%, and 13.5%), followed by White patients (34% 16.7%, 12.1%), Hispanic/Latinx patients (28.2%, 15.1%, 5.65%), and Asian patients (26.7%, 16.7%, 19.8%). 3 Interestingly, White patients presented with significantly more advanced stage disease in small intestine, colon, and rectal NENs (25%, 40%, 11.3%) than ethnically Hispanic/Latinx patients (25.6%, 27.5%, 6.5%), Black (18.1%, 35.3%, 7.2%), and Asian patients (18.8%, 35.3%, 6.5%), raising questions as to the etiology of these differences in GEP-NENs of various primary sites. 3 Regarding clinical outcomes, recent work has uncovered alarming disparities between White and minority GEP-NEN patients-particularly Black patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation